Modeling and Robust Fractional Order Fuzzy Sliding Mode Two Time Scale Controller Design for Synchronous Generator of ACP1000 Nuclear Power Plant in LabVIEW - Arshad Habib Malik; Feroza Arshad; Aftab Ahmad Memon (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2023)
A state-of-the-art higher-order model of a synchronous generator is developed for ACP1000 nuclear power plant in the present research. The model is transformed into state space form. The state space model is decomposed into the two-time scale framework. Based on the dynamics of the synchronous generator, fast and slow states are identified. The reduced order slow model is identified by neglecting the fast dynamics. A closed-loop model is developed in the frequency domain incorporating coupled and decoupled dynamics as separate transfer functions. The closed-loop model is configured as input-output pairs and two controllers are synthesized using a hybrid fraction order proportional integral derivative sliding surface oriented adaptive fuzzy two-time-scale control algorithm. The simulation model is developed in the graphical programming environment LabVIEW. The open and closed loop dynamics of the synchronous generator is simulated and analyzed in frequency and time domain separately. The proposed closed-loop framework is robust in performance, results are accurate and stable well within robust performance bounds.